2023
DOI: 10.3390/su151712684
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Impact of Team Interdependence on Cooperative Performance in Public–Private Partnership Projects: The Moderating Effect of Government Equity Participation

Han Zhang,
Shiying Shi,
Fangfang Zhao
et al.

Abstract: Sustainable collaboration among teams drives sustainable public–private partnership (PPP) projects, and the interactions, perceptions, and behaviors of project teams with ad hoc decision-making power critically impact collaborative performance in PPP contexts. While the role relationships between subjective interdependence, collective behaviors, team processes, and performance in PPP project teams are yet to be clarified, further validation is needed to embed this logic in project management. This study aims t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…Through direct effect testing (as shown in Figure 9), project governance shows a substantial positive correlation effect on governance performance, and governance performance is positively associated with project sustainability. In the three types of governance mechanism, the correlation of relational governance to governance performance shows the highest strength, while the correlation of contract governance and risk governance to governance performance is not as strong as that of relational governance, meaning that relationship rules play a crucial role in PPP projects mainly through improving the satisfaction of all parties related [25] (Lu et al, 2015). Notably, H1a has not been proven, meaning that the main parties in PPP projects tend to avoid potential risk that may emerge in future development.…”
Section: Hypotheses Testing 51 Direct Effect Testingmentioning
confidence: 98%
See 1 more Smart Citation
“…Through direct effect testing (as shown in Figure 9), project governance shows a substantial positive correlation effect on governance performance, and governance performance is positively associated with project sustainability. In the three types of governance mechanism, the correlation of relational governance to governance performance shows the highest strength, while the correlation of contract governance and risk governance to governance performance is not as strong as that of relational governance, meaning that relationship rules play a crucial role in PPP projects mainly through improving the satisfaction of all parties related [25] (Lu et al, 2015). Notably, H1a has not been proven, meaning that the main parties in PPP projects tend to avoid potential risk that may emerge in future development.…”
Section: Hypotheses Testing 51 Direct Effect Testingmentioning
confidence: 98%
“…Lu et al (2015) [24] concluded that both contract governance and relational governance can improve project governance performance based on transaction cost economics. Zhang proposed that team interdependence has a positive impact on cooperative performance in public-private partnership projects [25]. Risk governance is an important institutional arrangement to effectively resolve project conflicts and improve project performance [26].…”
Section: Governance Mechanism and Ppp Project Governance Performance ...mentioning
confidence: 99%
“…This credibility will fuel an escalation of commitment and cooperation in the following action phase, and thus improve performance. When tasks are interdependent, team members should interact closely with each other to accomplish the job, which provides them with more opportunities to demonstrate positive behaviors [28]. Thus, when tasks are inherently interdependent, team members are more motivated to reciprocate the benefits they receive from other members and put more effort into task performance.…”
Section: Introductionmentioning
confidence: 99%